Pengaruh Rotasi Pekerjaan, Pengembangan Karir dan Motivasi terhadap Kinerja Karyawan pada PT.Kemuning Group Cabang Medan II - Felice Mareta Waruwu; Natalia Leli Marni Gulo; Westiani Gulo; Yolanda Sarumaha; Maduma Sari Sagala (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of job rotation, career development and motivation on employee performance at PT. Kemuning Group Medan Branch II. The population in this study are employees at PT. Kemuning Group Branch Medan II, amounting to 56 people, while the determination technique using the saturated sampling method. The data sources in this study are primary and secondary data. And the data analysis technique used is quantitative analysis and multiple linear regression. The results of the multiple linear regression analysis are: Y = 21,162 + 0,496X1 + -0,146X2 + 0,543X3+e. The results of the t-test (partial): 1) job rotation, with a tcount value of 7.148 > ttable 1.674, so that compensation (X1) has a significant effect on employee performance (Y) partially. 2) career development with tcount 1.538 < ttable 1.674, so career development (X2) does not have a significant effect on employee performance (Y) partially. 3) motivation with a value of tcount 6.213 > ttable 1.674 so that motivation (X3) has a significant effect on employee performance (Y) partially. F count = 35.706 > F table 2.78. Then the coefficient of determination (R2) is 0.673 (67.3%). So that it can be said that 67.3% of the variation of the independent variables, namely job rotation, career development and motivation in the model can explain the variables of employee performance at PT. Kemuning Group Branch Medan II while the remaining 32.7% is influenced by other variables outside the model.